2019
DOI: 10.1038/s41598-019-41499-1
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone elevation on the day of hCG trigger has detrimental effect on live birth rate in low and intermediate ovarian responders, but not in high responders

Abstract: Progesterone elevation (PE) on the day of hCG trigger is associated with decreased pregnancy outcome in fresh cycles. Evidence for this comes from overall patient estimates that mostly ignore different ovarian responses. To compare the impacts of PE on the day of hCG trigger on live birth rates (LBs) in low, intermediate and high ovarian responders and to explore the cut-off value for PE in different populations according to the ovarian response, we retrospectively analyzed a total of 2,351 patients receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(75 reference statements)
0
21
1
Order By: Relevance
“…The observations were contrary to the study by (Al-Obaidi, et al [11] ) which showed that triggering day were markedly high with progesterone elevation than in the nonprogesterone elevation groups (Wu, et al [14] ). The explanation is that, when FSH is used in stimulation, it induces bearing of LH receptors in granulosa cells, which leads to increase sensitivity to the same LH, which in turn could conduct to create the rise of progesterone prematurely, even with low level of serum LH (Glamoclija, et al [15] ).…”
Section: Discussioncontrasting
confidence: 90%
“…The observations were contrary to the study by (Al-Obaidi, et al [11] ) which showed that triggering day were markedly high with progesterone elevation than in the nonprogesterone elevation groups (Wu, et al [14] ). The explanation is that, when FSH is used in stimulation, it induces bearing of LH receptors in granulosa cells, which leads to increase sensitivity to the same LH, which in turn could conduct to create the rise of progesterone prematurely, even with low level of serum LH (Glamoclija, et al [15] ).…”
Section: Discussioncontrasting
confidence: 90%
“…This supports the hypothesis that increasing P4 levels is a simple mass effect due to excess number of follicles, and therefore, PE is more likely in hyper-responders. [ 1 2 3 4 5 6 7 9 10 11 13 14 15 16 17 18 19 23 24 25 27 28 29 30 31 32 ] We noted higher pre-ovulatory P4 levels in hyper-responders but not higher PE rates, probably because the mean values were lower than the chosen cut-off to define PE. In addition, we did not find higher CPR in hyper-responders despite better COS characteristics and hormonal profiles, in contrast to the findings of previous studies.…”
Section: Discussionmentioning
confidence: 63%
“…It should be noted however that the clinical utility of P/MII ratio may be less in patients with low ovarian reserve who would have higher ratio mainly because of low number of available oocytes (denominator) and not necessarily high level of progesterone. It would therefore seem that high progesterone level alone as denoted by previous studies may be clinically relevant [33]. On the other hand a beneficial effect of adoption of freeze all policy in patients with low number of available embryos has not been proven by randomized clinical trials.…”
Section: Discussionmentioning
confidence: 88%